Hypertonic saline solution for control of elevated intracranial pressure in patients with exhausted response to mannitol and barbiturates - Horn, Peter; Münch, Elke; Vajkoczy, Peter; Herrmann, Peter; Quintel, Michael; Schilling, Lothar; Schmiedek, Peter; Schürer, Ludwig (Neurological research, 1999)
Critically elevated intracranial pressure (ICP) represents the most important cause of morbidity and mortality in patients suffering from severe traumatic brain injury (TBI) and is a serious complication after subarachnoid hemorrhage (SAH). Thus new strategies for the control of ICP are required. Based on the evidence available hypertonic saline solution (HSS) may be a promising approach. It was therefore the aim of the present study to evaluate in a prospective manner the effects of HSS on ICP and cerebral perfusion pressure (CPP) in patients with therapy-resistant elevation of ICP. A total of 48 bolus infusions of HSS (7.5%, 2 ml kg'1 b.w.; infusion rate 20 ml min*1) were given intravenously (range 1-15 per patient) to 10 patients (age 41 ±6 years) with TBI and SAH. Only patients with ICP > 25 mmHg not responding to standard ICP- management protocol and plasma sodium (Na+) concentration < 150 mmol I-1 were included in the study. Within the first hour after HSS application, ICP decreased from 33±9 mmHg to 19 ±6 mmHg (p < 0.05) and further to 18±5 mmHg at the time of maximum effect (98 ±11 min post bolus). Decrease of ICP was accompanied by a rise of CPP from 68±11 mmHg to 79±11 mmHg fp < 0.05) after 1 h and further to 81 ± 7 7 mmHg at the time of maximum effect. Plasma Na+ concentration was 141 ±6 mmol l 1 before and 143 ±5 mmol I-1 1 h after HSS bolus. Corresponding values for plasma osmolality were 302 ± 11 and 308 ± 12 mOsm t 1. When the ICP lowering effect was transient, subsequent HSS bolus was necessary 163 ±54 min after previous dosing. The present results indicate that repeated bolus application of HSS (7.5% NaCI, 2 ml kg b.w.) is an effective measure to decrease ICP which is otherwise refractory to standard therapeutic approaches. Whether or not the therapy scheme is also suited as primary measure for the control of ICP remains to be established. [Neurol Res 1999; 21: 758-764]
Published online: 21 Jul 2016
Gesehen am 24.03.2022